1999
DOI: 10.1093/brain/122.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Differential spatial memory impairment after right temporal lobectomy demonstrated using temporal titration

Abstract: In this study a temporal titration method to explore the extent to which spatial memory is differentially impaired following right temporal lobectomy was employed. The spatial and non-spatial memory of 19 left and 19 right temporal lobectomy (TL) patients was compared with that of 16 normal controls. The subjects studied an array of 16 toy objects and were subsequently tested for object recall, object recognition and memory for the location of the objects. By systematically varying the retention intervals for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(64 citation statements)
references
References 50 publications
6
58
0
Order By: Relevance
“…More studies have examined spatial memory for a combination of positional information and object identities. For example, various authors have investigated the relocation of toy objects on a table top in patients with hippocampal lesions, commonly demonstrating a righthippocampal involvement (Nunn et al, 1999;Smith & Milner, 1989). In general, the current findings corroborate and extend previous results with similar paradigms.…”
Section: Discussionsupporting
confidence: 89%
“…More studies have examined spatial memory for a combination of positional information and object identities. For example, various authors have investigated the relocation of toy objects on a table top in patients with hippocampal lesions, commonly demonstrating a righthippocampal involvement (Nunn et al, 1999;Smith & Milner, 1989). In general, the current findings corroborate and extend previous results with similar paradigms.…”
Section: Discussionsupporting
confidence: 89%
“…This interpretation is in agreement with reports showing less efficient encoding in elderly adults (Grady et al, 1995;Stebbins et al, 2002), was however not confirmed in a control study on a different group of subjects (Park et al, 1990). Interestingly, object location memory was shown to be dependent on the MTL region (Nunn et al, 1999;Pillon et al, 1999;Stepankova et al, 2004) or more specifically on the parahippocampal gyrus (Maguire et al, 1998b;Owen et al, 1996). Thus another interpretation of this age dependent object location memory deficit may attribute it to the decline in MTL activity.…”
Section: Spatial Memory and Navigationsupporting
confidence: 78%
“…Object location memory on this task has been shown to be sensitive to hippocampal lesions (Nunn et al, 1999;Smith & Milner, 1981, 1989 hence the female advantage on this measure suggest sex-related differences in allocentric spatial memory dependent on hippocampal function. Supporting this possibility, sex differences in the size of the hippocampus have been previously reported; females possessing larger hippocampal volumes than males (Filipek et al, 1994;Giedd et al, 1997).…”
Section: Discussionmentioning
confidence: 86%
“…To our knowledge this is the first study to examine sexual orientation related effects in object location memory. Moreover, the Smith and Milner task has been shown to be sensitive to temporal lobe lesions and performance is dependant on the extent of hippocampal resection (Nunn et al, 1999;Smith & Milner, 1981, 1989. Hence, this is the first study to investigate sexual orientation related differences in cognitive functions dependent on the hippocampal regions.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation